Dakwah dan Pengembangan Kendali Diri: Upaya Antisipasi Kecenderungan Seks Bebas Remaja - Hajir Tajiri (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2010)
Da’wah in context preventing of freesexual behavior on teenager is something not easy. Da’wah in this context need creative efforts either individual or collective and  collaborative of all profesion and government policy. One of suitable approach is cognitive-behavioral, with this approach estimated will able giving solution to teenager problem, especially to increase self control ability as prevention step  to freesexual tendency. That is by cognition restructurization or modification and rebuild their behavior.